Ultrathin hydrophilic / hydrophobic ZnO-CuS-CC photo-thermal material as well as preparation method and application thereof
By using ultra-thin/hydrophobic ZnO-CuS@CC photothermal materials in solar interface evaporators, the problems of salt ion enrichment and organic pollutant treatment are solved, efficient photothermal water evaporation and photocatalytic degradation are achieved, and the stability and environmental performance of the evaporator are improved.
Patent Information
- Application Number
- CN202411860242.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
When existing solar interface evaporators are used for a long time or treated with high concentrations of salt water and wastewater, they are prone to salt ion enrichment and deposition, which affects the evaporation rate and service life. At the same time, simply evaporating organic pollutants will lead to aggravation of pollution.
Ultrathin/hydrophobic ZnO-CuS@CC photothermal material is used, which is composed of an ultrathin ZnO-CuS hydrophilic layer grown on a hydrophobic substrate. The hydrophilic layer contains CuS nanosheets and attached ZnO nanoparticles, forming a large number of micropores and chambers, improving light absorption and achieving photocatalytic degradation.
It realizes efficient photothermal water evaporation and photocatalytic degradation of organic pollutants, avoids salt ion deposition, improves the stability and service life of the evaporator, and promotes the recycling of water resources.
Smart Images

Figure CN119680578A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photothermal evaporators, and in particular relates to an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material and a preparation method and application thereof. Background Art
[0002] Due to global climate change, social development and population growth, fresh water and energy resources, as one of the indispensable parts of human production and life, are in serious shortage. Using clean energy to desalinate seawater can increase the supply of fresh water. Seawater accounts for about 97% of the world's water resources, while fresh water for human consumption accounts for only 2.5%. Therefore, there is an urgent need for technologies to extract clean water from seawater and wastewater. Compared with the high investment cost and increased carbon emissions of typical traditional fossil fuel thermal distillation processes, solar interfacial evaporation (SIE) technology converts solar energy into thermal energy through photothermal materials, confining heat to the air-water interface, effectively suppressing heat loss, and improving water evaporation rate and photothermal conversion efficiency. Therefore, solar-driven interfacial evaporation is considered to be a low-cost, environmentally friendly and sustainable technology to solve the problem of water shortage, and has good application prospects in the field of water treatment. In the past few years, SIE has made substantial progress in the development of advanced photothermal materials, such as metal plasmas, carbon-based materials and polymers. Among them, SIE based on carbon cloth has great potential in practical applications. By treating the surface fibers of carbon cloth to make its surface contain a large number of pores, it helps to increase the specific surface area while further improving the solar absorption efficiency and water transmission performance.
[0003] Water pollution has become the most concerning environmental problem in the global environment. Photocatalytic degradation can degrade a variety of organic pollutants into harmless products (e.g., CO2, H2O) and has been proven to be an efficient, green and promising sewage purification technology. Photocatalytic degradation refers to the process in which a catalyst absorbs photons in the presence of a catalyst and generates strong oxidizing / reducing free radicals through a chain reaction, leading to the degradation of substances. Traditional powdered photocatalysts are difficult to collect and recycle after use and are prone to secondary pollution. Therefore, the growth of nanostructured photocatalysts on suitable substrates has received widespread attention.
[0004] In addition to using seawater as an evaporating water body to obtain fresh water, if solar interfacial evaporation can be used to treat and recycle the large amount of wastewater generated in human daily life, the high-concentration brine in industrial production, and the wastewater containing toxic, harmful, and difficult-to-naturally degrade organic pollutants, it will have important practical significance for saving water resources and being environmentally friendly.
[0005] However, in the long-term use of existing solar interfacial evaporators, or in the evaporation process of treating high-concentration brine or high-concentration wastewater, due to insufficient water supply or difficulty in salt ion reflux, salt ions are enriched on the surface of the evaporator to form salt deposits, thereby affecting the evaporation rate and the service life of the evaporator. As for organic pollutants, directly treating organic wastewater through solar evaporation alone will cause the organic pollutants in the wastewater to concentrate after evaporation, leading to more serious pollution. Therefore, the development of a method that can simultaneously achieve efficient evaporation, brine collection, and degradation of organic pollutants has important application value. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material and a preparation method and application thereof, so as to solve the technical problems in the prior art of how to prevent salt deposition, effectively treat organic pollutants and achieve efficient evaporation.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention provides an ultrathin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, comprising a hydrophobic substrate, an ultrathin ZnO-CuS hydrophilic layer grown on the upper surface of the hydrophobic substrate, the ultrathin ZnO-CuS hydrophilic layer comprising CuS nanosheets and ZnO nanoparticles attached to the CuS nanosheets, a large number of microscopic pores and cavities are formed on the surface of the ultrathin ZnO-CuS hydrophilic layer, the existence of the microscopic pores and cavities constructs light traps, and the ZnO nanoparticles reduce light reflection and improve light absorption rate.
[0009] In one embodiment, the thickness of the ultra-thin ZnO-CuS hydrophilic layer is 300 nm±5.
[0010] The present invention also provides a method for preparing an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, comprising the following steps:
[0011] Preparation of a hydrophobic substrate with a single-sided ultra-thin copper coating;
[0012] Sodium hydroxide pellets and sulfur powder were mixed in DMF, and deionized water was added to prepare a yellow mixed solution;
[0013] The hydrophobic substrate with a single-sided ultra-thin copper plating layer is immersed in a yellow mixed solution, and the single-sided ultra-thin copper plating layer reacts to form copper sulfide nanosheets, which are then rinsed and dried to obtain a hydrophobic substrate with a copper sulfide nanosheet layer grown thereon;
[0014] Zinc oxide was sputtered onto one side of a copper sulfide nanosheet layer grown on a hydrophobic substrate on which the copper sulfide nanosheet layer was grown to prepare a ZnO-CuS@CC photothermal material.
[0015] In one embodiment, the hydrophobic substrate is a hydrophobic carbon cloth.
[0016] In one embodiment, the process of preparing a hydrophobic substrate with a single-sided ultra-thin copper plating layer is as follows:
[0017] The cleaned hydrophobic substrate is fixed to the magnetron sputtering equipment, and a copper target is placed. After vacuuming, argon gas is introduced to pre-sputter and clean the oxide on the surface of the copper target. Then, sputtering is performed for 5-20 minutes to plate copper on the hydrophobic carbon cloth to obtain a hydrophobic substrate with a single-sided ultra-thin copper-plated layer.
[0018] In one embodiment, the single-sided ultra-thin copper plating layer has a thickness of 80-100 nm.
[0019] In one embodiment, the copper sulfide nanosheet layer has a thickness of 210-220 nm.
[0020] In one embodiment, the usage ratio of the sodium hydroxide, sulfur powder and DMF is 2:1:2, and the volume ratio of the DMF to deionized water is 1:15.
[0021] In one embodiment, the process of sputtering zinc oxide onto one side of the hydrophobic substrate on which the copper sulfide nanosheet layer is grown is as follows:
[0022] The rotation speed of the hydrophobic substrate for growing copper sulfide nanosheets is 13r / min, and a DC power supply is used to sputter a Zn target. 30sccm-50sccm argon and 15sccm-30sccm oxygen are introduced. The power supply is started under a vacuum degree of 0.6Pa, the current is 0.2A-0.3A, the sputtering power is 40W-80W, and a glow discharge is initiated on the surface of the Zn target for sputtering for 5min-10min.
[0023] The present invention also provides an application of the above-mentioned ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material in a photothermal evaporator, wherein the photothermal evaporator comprises an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, a water storage tank and an outlet tank respectively provided with dust-free cloths, wherein the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material is constructed as a bridge between the water storage tank and the outlet tank and is overlapped with the dust-free cloths respectively provided on the water storage tank and the outlet tank.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention provides an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material. The photothermal evaporator using the material can simultaneously realize the two functions of efficient photothermal water evaporation and photocatalytic degradation of organic pollutants. The ZnO-CuS heterojunction acts as a photocatalyst to absorb light with sufficient energy, so that electrons are excited from the valence band to the conduction band, generating electron-hole pairs. The photogenerated electrons and holes react with water, surface hydroxyl groups and O2 to generate active free radicals, such as hydroxyl radicals (·OH) and superoxide radicals (·O2 - ). These free radicals react with pollutant molecules adsorbed on the catalyst surface to oxidize and decompose the pollutants into CO2, H2O and other light byproducts. It can be applied to seawater desalination and wastewater treatment. Both CuS and ZnO have excellent catalytic properties. Combining the two to form a heterojunction photocatalyst is of great significance to improve the photocatalytic efficiency.
[0026] The present invention prepares an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, which is applied to a solar evaporator to achieve efficient photothermal conversion efficiency and evaporation rate. By growing an ultra-thin ZnO-CuS hydrophilic layer (thickness is only about 300nm) on a hydrophobic substrate, a small amount of water can be confined to the evaporation interface to form a thin water film. The ZnO-CuS@CC photothermal material also has good light absorption performance, which can convert solar energy into thermal energy, so that the heat is localized on the thinner water film on the surface of the evaporator, thereby reducing the heat conduction loss to the large volume of water, so that the surface can achieve rapid evaporation. Driven by rapid evaporation, a large number of chambers and pores on the surface of the hydrophilic layer are rapidly replenished through capillary action, ensuring a continuous supply of water and achieving efficient water evaporation.
[0027] The ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal evaporator prepared by the present invention has stability for evaporation of high-concentration brine. The salt ions are quickly conducted from the liquid storage tank to the surface of the photothermal material for evaporation by a one-way conduction method. The microporous structure on the surface of the ZnO-CuS@CC photothermal material promotes the rapid discharge of salt ions into the export liquid pool. A large amount of salt ions are discharged into the export liquid pool, so that there is no salt deposition on the surface, ensuring the rapid evaporation and the stable operation of the evaporator, and the effect of brine concentration can be achieved. Multiple cycles will eventually achieve zero liquid discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM morphology image of the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material prepared in Example 1 of the present invention;
[0029] Figure 2 This is a contact angle photo of the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material of the present invention;
[0030] Figure 3 It is a schematic diagram of the photothermal evaporator of the present invention;
[0031] Figure 4 This is the evaporation performance diagram of the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal evaporator of the present invention;
[0032] Figure 5 This is a photothermal catalytic performance diagram of the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC of the present invention. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0035] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0036] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0037] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0038] On one hand, the present invention provides an ultrathin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, comprising an ultrathin ZnO-CuS hydrophilic layer grown on the upper surface of a hydrophobic substrate, the ultrathin ZnO-CuS hydrophilic layer comprising CuS nanosheets and ZnO nanoparticles attached to the CuS nanosheets, a large number of microscopic pores and cavities are formed on the surface of the ultrathin ZnO-CuS hydrophilic layer, the presence of the microscopic pores and cavities constructs a light trap, and the ZnO nanoparticles reduce light reflection and improve light absorption rate.
[0039] One of the inventive points of the present invention is that the thickness of the ultra-thin ZnO-CuS hydrophilic layer is about 300 nm.
[0040] First, the zinc oxide and copper sulfide in the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material are both semiconductor materials, and can be used as photocatalysts alone. The two are combined to form a heterojunction. At the heterojunction interface, the charges between different materials will be transferred and rearranged to form "holes" with high electron affinity and "electrons" with low electron affinity. This uneven charge distribution makes the heterojunction catalytic and can accelerate the chemical reaction. The grain boundaries of the heterojunction often contain more active sites, which are easy to adsorb reactants and discharge products, thereby improving the catalytic efficiency. Secondly, the addition of ZnO can reduce the reflectivity of the photothermal material and improve the light absorption capacity. At the same time, many oxide groups, such as hydroxyl groups, often appear on the surface of zinc oxide. These groups can hydrogen bond with water molecules, thereby showing hydrophilicity. Therefore, the addition of zinc oxide can increase the hydrophilicity of CuS@CC and help water transport during the evaporation process.
[0041] Another aspect of the present invention provides a method for preparing an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, comprising the following steps:
[0042] A hydrophobic substrate with a single-sided ultra-thin copper-plated layer having a copper-plated layer thickness of 80 to 100 nm is obtained;
[0043] The specific process of preparing a hydrophobic substrate with a single-sided ultra-thin copper plating layer is as follows: fix the cleaned hydrophobic substrate to a magnetron sputtering device, place a copper target, introduce argon gas after vacuuming, pre-sputter clean the oxide on the surface of the copper target, then sputter for 5-20 minutes, plate copper on the hydrophobic carbon cloth, and prepare a hydrophobic substrate with a single-sided ultra-thin copper plating layer.
[0044] Sodium hydroxide and sulfur powder are mixed in DMF, and deionized water is added to prepare a yellow mixed solution. Specifically, the dosage ratio of sodium hydroxide, sulfur powder and DMF is 2:1:2, and the volume ratio of DMF to deionized water is 1:15.
[0045] The hydrophobic substrate with a single-sided ultra-thin copper plating layer is immersed in a yellow mixed solution, and the single-sided ultra-thin copper plating layer reacts to generate copper sulfide nanosheets, which are then rinsed and dried to obtain a hydrophobic substrate with a copper sulfide nanosheet layer, wherein the thickness of the copper sulfide nanosheet layer is 210 to 220 nm.
[0046] Zinc oxide is sputtered onto the surface of the hydrophobic substrate on which the copper sulfide nanosheet layer is grown to obtain a ZnO-CuS@CC photothermal material. Specifically, the rotation speed of the hydrophobic substrate on which the copper sulfide nanosheet layer is grown is 13r / min, a direct current power supply is used to sputter a Zn target, 30-50sccm argon and 15-30sccm oxygen are introduced, the power supply is started under a vacuum degree of 0.6Pa, the current is 0.2-0.3A, the sputtering power is 40-80W, and a glow discharge is initiated on the surface of the Zn target for 5-10min.
[0047] On the other hand, the present invention provides a photothermal evaporator, which includes an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, a water storage tank and a derivation tank each provided with a dust-free cloth. The ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material is constructed as a bridge between the water storage tank and the derivation tank and is overlapped with the dust-free cloths constructed on the water storage tank and the derivation tank respectively.
[0048] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0049] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0050] Example 1
[0051] This embodiment provides an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material and a preparation method thereof. The following is a preparation method of the ZnO-CuS@CC photothermal material:
[0052] Step 1: First, the hydrophobic carbon cloth (size 10 cm×10 cm) is ultrasonically cleaned to remove impurities and contaminants on the surface.
[0053] Step 2: Fix the cleaned hydrophobic carbon cloth onto the workbench of the magnetron sputtering equipment, close the baffle, put in a copper target with a purity of 99.99%, and evacuate to 1.8×10 -3Pa, introduce 50sccm argon, turn on the DC power supply, set the current to 0.2A, the power to 80W, and discharge the Cu target surface for 5 minutes to remove the oxide on the surface of the copper target. Set the rotation speed of the workbench to 9r / min, open the baffle, and sputter for 5 minutes to obtain a hydrophobic carbon cloth with a single-sided ultra-thin copper coating.
[0054] Step 3: 0.5 mL of DMF was measured in a beaker, and then 0.5 g of sodium hydroxide and 0.2 g of sulfur powder were weighed in the beaker containing DMF, 20 mL of deionized water was added, and the mixture was heated and stirred at 50° C. for 20 min to obtain a yellow mixed solution.
[0055] Step 4: After the solution is cooled to room temperature, immerse the hydrophobic carbon cloth with a single-sided ultra-thin copper coating into the solution. After reacting for 1-2 seconds, the side containing the coating quickly turns black to generate copper sulfide nanosheets. Then rinse the surface with propanol and deionized water and dry it in a drying oven at 60°C for 6 hours.
[0056] Step 5: Continue to sputter zinc oxide on the hydrophobic carbon cloth grown with copper sulfide nanosheets using a magnetron sputtering device, using a Zn target with a purity of 99.99%, and a rotation speed of 13r / min for the hydrophobic carbon cloth grown with copper sulfide nanosheets. Use a DC power supply to sputter the Zn target, introduce 50sccm argon and 30sccm oxygen, start the power supply under a vacuum of 0.6Pa, the current is 0.2A, the sputtering power is 40W, and the Zn target surface is glowing and discharged for 10min.
[0057] After the above five steps, ZnO-CuS@CC photothermal material was obtained.
[0058] CuS nanosheets and ZnO nanoparticles grow on the upper surface of the photothermal material, which has good wetting properties, while the lower surface remains hydrophobic.
[0059] This embodiment provides a solar evaporator using the above-mentioned material, which includes a ZnO-CuS@CC photothermal material and a dust-free cloth. The ZnO-CuS@CC photothermal material (with a size of 3×2 cm) is built as a bridge between a water storage tank filled with a solution and a dewatering tank. Dust-free cloths of the same width are carried on both sides to supply and dewater water, forming a unidirectional flow evaporator.
[0060] Example 2
[0061] This embodiment provides an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material and a preparation method thereof. The following is a preparation method of the ZnO-CuS@CC photothermal material:
[0062] Step 1: First, the hydrophobic carbon cloth (size 10 cm×10 cm) is ultrasonically cleaned to remove impurities and contaminants on the surface.
[0063] Step 2: Fix the cleaned hydrophobic carbon cloth onto the workbench of the magnetron sputtering equipment, close the baffle, put in a copper target with a purity of 99.99%, and evacuate to 1.8×10 -3 Pa, introduce 50sccm argon, turn on the DC power supply, set the current to 0.2A, the power to 80W, and discharge the Cu target surface for 5 minutes to remove the oxide on the surface of the copper target. Set the rotation speed of the workbench to 9r / min, open the baffle, and sputter for 10 minutes to obtain a hydrophobic carbon cloth with a single-sided ultra-thin copper coating.
[0064] Step 3: 0.5 mL of DMF was measured in a beaker, and then 0.5 g of sodium hydroxide and 0.2 g of sulfur powder were weighed in the beaker containing DMF, 20 mL of deionized water was added, and the mixture was heated and stirred at 50° C. for 20 min to obtain a yellow mixed solution.
[0065] Step 4: After the solution is cooled to room temperature, immerse the hydrophobic carbon cloth with a single-sided ultra-thin copper coating into the solution. After reacting for 1-2 seconds, the side containing the coating quickly turns black to generate copper sulfide nanosheets. Then rinse the surface with propanol and deionized water and dry it in a drying oven at 60°C for 6 hours.
[0066] Step 5: Continue to sputter zinc oxide on the hydrophobic carbon cloth grown with copper sulfide nanosheets using a magnetron sputtering device, using a Zn target with a purity of 99.99%, and a rotation speed of 13r / min for the hydrophobic carbon cloth grown with copper sulfide nanosheets. Use a DC power supply to sputter the Zn target, introduce 30sccm argon and 15sccm oxygen, start the power supply under a vacuum of 0.6Pa, the current is 0.3A, the sputtering power is 80W, and the Zn target surface is glowing and discharged for 5min.
[0067] After the above five steps, ZnO-CuS@CC photothermal material was obtained.
[0068] CuS nanosheets and ZnO nanoparticles grow on the upper surface of the photothermal material, which has good wetting properties, while the lower surface remains hydrophobic.
[0069] This embodiment provides a solar evaporator using the above-mentioned material, which includes a ZnO-CuS@CC photothermal material and a dust-free cloth. The ZnO-CuS@CC photothermal material (with a size of 3×2 cm) is built as a bridge between a water storage tank filled with a solution and a dewatering tank. Dust-free cloths of the same width are carried on both sides to supply and dewater water, forming a unidirectional flow evaporator.
[0070] Example 3
[0071] This embodiment provides an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material and a preparation method thereof. The following is a preparation method of the ZnO-CuS@CC photothermal material:
[0072] Step 1: First, the hydrophobic carbon cloth (size 10 cm×10 cm) is ultrasonically cleaned to remove impurities and contaminants on the surface.
[0073] Step 2: Fix the cleaned hydrophobic carbon cloth onto the workbench of the magnetron sputtering equipment, close the baffle, put in a copper target with a purity of 99.99%, and evacuate to 1.8×10 -3 Pa, 50sccm argon was introduced, the DC power supply was turned on, the current was set to 0.2A, the power was set to 80W, the Cu target surface was ignited and discharged, and the oxide on the surface of the copper target was removed by bombardment for 5 minutes. The rotation speed of the workbench was set to 9r / min, and then the baffle was opened and sputtered for 15 minutes to obtain a hydrophobic carbon cloth with a single-sided ultra-thin copper coating.
[0074] Step 3: 0.5 mL of DMF was measured in a beaker, and then 0.5 g of sodium hydroxide and 0.2 g of sulfur powder were weighed in the beaker containing DMF, 20 mL of deionized water was added, and the mixture was heated and stirred at 50° C. for 20 min to obtain a yellow mixed solution.
[0075] Step 4: After the solution is cooled to room temperature, immerse the hydrophobic carbon cloth with a single-sided ultra-thin copper coating into the solution. After reacting for 1-2 seconds, the side containing the coating quickly turns black to generate copper sulfide nanosheets. Then rinse the surface with propanol and deionized water and dry it in a drying oven at 60°C for 6 hours.
[0076] Step 5: Continue to sputter zinc oxide on the hydrophobic carbon cloth grown with copper sulfide nanosheets using a magnetron sputtering device, using a Zn target with a purity of 99.99%, and a rotation speed of 13r / min for the hydrophobic carbon cloth grown with copper sulfide nanosheets. Use a DC power supply to sputter the Zn target, introduce 50sccm argon and 30sccm oxygen, start the power supply under a vacuum of 0.6Pa, the current is 0.2A, the sputtering power is 40W, and the Zn target surface is glowing and discharged for 5min.
[0077] After the above five steps, ZnO-CuS@CC photothermal material was obtained.
[0078] CuS nanosheets and ZnO nanoparticles grow on the upper surface of the photothermal material, which has good wetting properties, while the lower surface remains hydrophobic.
[0079] This embodiment provides a solar evaporator using the above-mentioned material, which includes a ZnO-CuS@CC photothermal material and a dust-free cloth. The ZnO-CuS@CC photothermal material (with a size of 3×2 cm) is built as a bridge between a water storage tank filled with a solution and a dewatering tank. Dust-free cloths of the same width are carried on both sides to supply and dewater water, forming a unidirectional flow evaporator.
[0080] Example 4
[0081] This embodiment provides an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material and a preparation method thereof. The following is a preparation method of the ZnO-CuS@CC photothermal material:
[0082] Step 1: First, the hydrophobic carbon cloth (size 10 cm×10 cm) is ultrasonically cleaned to remove impurities and contaminants on the surface.
[0083] Step 2: Fix the cleaned hydrophobic carbon cloth onto the workbench of the magnetron sputtering equipment, close the baffle, put in a copper target with a purity of 99.99%, and evacuate to 1.8×10 -3 Pa, introduce 50sccm argon, turn on the DC power supply, set the current to 0.2A, the power to 80W, and discharge the Cu target surface for 5 minutes to remove the oxide on the surface of the copper target. Set the rotation speed of the workbench to 9r / min, open the baffle, and sputter for 20 minutes to obtain a hydrophobic carbon cloth with a single-sided ultra-thin copper coating.
[0084] Step 3: Measure 0.5 mL of DMF into a beaker, then weigh 0.5 g of sodium hydroxide and 0.2 g of sulfur powder into the beaker containing DMF, add 20 mL of deionized water, heat and stir at 50°C for 20 min to obtain a yellow mixed solution.
[0085] Step 4: After the solution is cooled to room temperature, immerse the hydrophobic carbon cloth with a single-sided ultra-thin copper coating into the solution. After reacting for 1-2 seconds, the side containing the coating quickly turns black to generate copper sulfide nanosheets. Then rinse the surface with propanol and deionized water and dry it in a drying oven at 60°C for 6 hours.
[0086] Step 5: Continue to sputter zinc oxide on the hydrophobic carbon cloth grown with copper sulfide nanosheets using a magnetron sputtering device, using a Zn target with a purity of 99.99%, and a rotation speed of 13r / min for the hydrophobic carbon cloth grown with copper sulfide nanosheets. Use a DC power supply to sputter the Zn target, introduce 50sccm argon and 30sccm oxygen, start the power supply under a vacuum of 0.6Pa, the current is 0.2A, the sputtering power is 40W, and the Zn target surface is glowing and discharged for 10min.
[0087] After the above five steps, ZnO-CuS@CC photothermal material was obtained.
[0088] CuS nanosheets and ZnO nanoparticles grow on the upper surface of the photothermal material, which has good wetting properties, while the lower surface remains hydrophobic.
[0089] This embodiment provides a solar evaporator using the above-mentioned material, which includes a ZnO-CuS@CC photothermal material and a dust-free cloth. The ZnO-CuS@CC photothermal material (with a size of 3×2 cm) is built as a bridge between a water storage tank filled with a solution and a dewatering tank. Dust-free cloths of the same width are carried on both sides to supply and dewater water, forming a unidirectional flow evaporator.
[0090] Figure 1 The SEM surface morphology and EDS spectrum of the ZnO-CuS@CC photothermal material prepared in Example 1 of the present invention. As shown in Figure a, the original hydrophobic carbon cloth fiber has a smooth surface and a diameter of about 8 μm. Through magnetron sputtering of Cu (the thickness of the copper layer on the fiber surface is between 80-100 nm, as shown in Figure e) and redox method, a large number of copper sulfide nanosheets are grown on the surface of the carbon cloth fiber (Figure b), and a large number of microscopic pores and cavities are formed on the surface, with a thickness of about 210 nm (Figure f). The existence of these pores and cavities constructs light traps and significantly improves the light absorption characteristics. After that, a large number of ZnO nanoparticles are attached to the surface of the copper sulfide nanosheets by magnetron sputtering zinc. The ZnO-CuS@CC photothermal material was generated (Figure c, the inset is a local magnified view). The ZnO-CuS on the surface formed an ultra-thin hydrophilic layer with a thickness of only about 300nm (Figure g), which is conducive to the formation of a thin water film on the surface, accelerating the diffusion of capillary water and the transmission of solutes. ZnO nanoparticles can reduce light reflection and further improve the light absorption performance of the material. The EDS energy spectrum shown in Figure d shows the presence of Zn, Cu, O, S and other elements in the photothermal material, further proving the successful preparation of the ZnO-CuS@CC photothermal material.
[0091] Figure 2 This is a water contact angle test diagram of the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material. As can be seen from the figure, 50μL of water droplets were dropped on the upper and lower surfaces of the ZnO-CuS@CC photothermal material, and the hydrophilic layer of the growing ZnO-CuS nanomaterial was completely absorbed after 0.2s, while the untreated bottom carbon cloth still remained hydrophobic. It proves that the obtained ZnO-CuS@CC photothermal material has the wetting properties of the upper layer being hydrophilic and the lower layer being hydrophobic, and the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material was successfully prepared.
[0092] Figure 3Schematic diagram of ZnO-CuS@CC photothermal material for catalysis and evaporation. Driven by the evaporation of the liquid surface and solar interface at both ends, the solution can be pumped from the storage liquid pool to the surface of the ZnO-CuS@CC photothermal material through the capillary action of the dust-free cloth, forming a thin water film on the ZnO-CuS@CC photothermal material and continuing to use the dust-free cloth to transfer the solution to the export liquid pool on the other side. In this one-way conduction process, the evaporation, concentration and photocatalytic degradation of organic pollutants of brine can be achieved.
[0093] Figure 4 The evaporation rate and mass loss of the ZnO-CuS@CC photothermal evaporator in 15% concentrated brine. As shown in the figure, under one sun radiation, the average evaporation rate of the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal evaporator for 15wt% NaCl solution with unidirectional conduction is 2.47kg m -2 ·h -1 , indicating that the ZnO-CuS@CC photothermal evaporator has good photothermal conversion performance and water transmission performance. At the same time, its evaporation rate only fluctuates in a small range within 2 hours and has no downward trend, indicating that no salt crystals are produced on the surface of the ZnO-CuS@CC photothermal material, further proving that the evaporator is stable and durable for the evaporation of high-concentration brine.
[0094] Figure 5 The photocatalytic degradation performance of ZnO-CuS@CC photothermal evaporator on organic pollutants. On the surface of ZnO-CuS@CC photothermal material, n-type semiconductor ZnO particles are attached to p-type semiconductor CuS nanosheets to form a ZnO-CuS heterostructure, which has good photocatalytic activity for the degradation of Rhodamine B (RhB). As can be seen from the figure, ZnO-CuS@CC photothermal evaporator can simultaneously realize the evaporation and photocatalytic degradation of RhB organic pollutants with a concentration of 10 mg / L. After five cycles of evaporation and photocatalysis, the evaporator after adsorption and analysis can achieve a degradation efficiency of more than 85% for RhB solution, showing a good dual function of evaporation and photocatalytic degradation of organic pollutants.
[0095] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. An ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, characterized in that: The invention comprises a hydrophobic substrate, an ultrathin ZnO-CuS hydrophilic layer is grown on the upper surface of the hydrophobic substrate, the ultrathin ZnO-CuS hydrophilic layer comprises CuS nanosheets and ZnO nanoparticles attached to the CuS nanosheets, a large number of microscopic pores and cavities are formed on the surface of the ultrathin ZnO-CuS hydrophilic layer, and the existence of the microscopic pores and cavities constructs a light trap.
2. The ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to claim 1, characterized in that: The thickness of the ultra-thin ZnO-CuS hydrophilic layer is 300nm±5.
3. A method for preparing the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to any one of claims 1 to 2, characterized in that: The following steps are involved: Preparation of a hydrophobic substrate with a single-sided ultra-thin copper coating; Sodium hydroxide pellets and sulfur powder were mixed in DMF, and deionized water was added to prepare a yellow mixed solution; The hydrophobic substrate with a single-sided ultra-thin copper plating layer is immersed in a yellow mixed solution, and the single-sided ultra-thin copper plating layer reacts to form copper sulfide nanosheets, which are then rinsed and dried to obtain a hydrophobic substrate with a copper sulfide nanosheet layer grown thereon; Zinc oxide was sputtered onto one side of a copper sulfide nanosheet layer grown on a hydrophobic substrate on which the copper sulfide nanosheet layer was grown to prepare a ZnO-CuS@CC photothermal material.
4. The method for preparing the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to claim 3, characterized in that: The hydrophobic substrate is a hydrophobic carbon cloth.
5. The method for preparing the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to claim 3, characterized in that: The process of preparing a hydrophobic substrate with a single-sided ultra-thin copper plating layer is as follows: The cleaned hydrophobic substrate is fixed to the magnetron sputtering equipment, and a copper target is placed. After vacuuming, argon gas is introduced to pre-sputter and clean the oxide on the surface of the copper target. Then, sputtering is performed for 5-20 minutes to plate copper on the hydrophobic carbon cloth to prepare a hydrophobic substrate with a single-sided ultra-thin copper plating layer.
6. The method for preparing the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to claim 3, characterized in that: The thickness of the single-sided ultra-thin copper plating layer is 80-100 nm.
7. The method for preparing the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to claim 3, characterized in that: The thickness of the copper sulfide nanosheet layer is 210-220 nm.
8. The method for preparing the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to claim 3, characterized in that: The dosage ratio of the sodium hydroxide, sulfur powder and DMF is 2:1:2, and the volume ratio of the DMF to deionized water is 1:
15.
9. The method for preparing the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to claim 3, characterized in that: The process of sputtering zinc oxide onto one side of the hydrophobic substrate on which the copper sulfide nanosheet layer is grown is as follows: The rotation speed of the hydrophobic substrate for growing the copper sulfide nanosheet layer is 13r / min, and a DC power supply is used to sputter the Zn target. 30sccm-50sccm argon and 15sccm-30sccm oxygen are introduced. The power supply is started under a vacuum degree of 0.6Pa, the current is 0.2A-0.3A, the sputtering power is 40W-80W, and a glow discharge is initiated on the surface of the Zn target for 5min-10min.
10. An application of the ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material according to any one of claims 1 to 2 in a photothermal evaporator, characterized in that: The photothermal evaporator comprises an ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material, a water storage tank and an outlet tank respectively provided with dust-free cloths. The ultra-thin hydrophilic / hydrophobic ZnO-CuS@CC photothermal material is constructed as a bridge between the water storage tank and the outlet tank and is overlapped with the dust-free cloths respectively provided on the water storage tank and the outlet tank.
Citation Information
Patent Citations
Application of photothermal-conversion cupric sulfidecomposite film in water treatment
CN107235591A
Preparation method of photo-thermal distillation membrane with catalytic function
CN113680216A
Efficient photo-thermal conversion hydrophilic / hydrophobic fiber felt and preparation method thereof
CN115198519A
Integrated multifunctional solar evaporator and preparation method thereof
CN117209000A
Wettability-adjustable Janus structure photo-thermal fabric as well as preparation method and application thereof
CN119145215A
Cited By
Wettability-adjustable Janus structure photo-thermal fabric as well as preparation method and application thereof
CN119145215A
A Janus structure photothermal fabric with adjustable wettability and its preparation method and application
CN119145215B
Biomass photo-thermal interface evaporation material based on Cu-Zn-S photo-thermal catalytic layer as well as preparation method and application of biomass photo-thermal interface evaporation material
CN120987411A